Effect of Strong Mining on the Fracture Evolution Law of Trick Rise in the Mining Field and Its Control Technology - Zhaolin Li; Lianguo Wang; Ke Ding (Geofluids)
This study investigates the law of stress field and fracture field of the surrounding rock at the trick rise of the mining area affected by strong mining. It is found that as the working face continues to approach, large-scale cracks occur in the surrounding rock on the track rise. In particular, when the working face crosses the track rise, the equivalent stress τoct concentration area expands, gradually intersecting with the surrounding rock concentration area of the roadway. It indicates that the working face advancement caused a dramatic change in the stress field of the roadway envelope, which will have an immediate adverse effect on the track rise. With comprehensive support costs, economic efficiency, and other factors, the working face will no longer cross the track rise, and the stopping line is roughly controlled at -20 m so that the track rise can serve other working faces for a long time. The reinforcement support scheme of “anchor mesh spray + grouting anchor” is proposed for the key areas such as arch shoulder. Through the analysis of the field monitoring of the roadway surface displacement, the deformation of the roadway surrounding rock showed a change trend of increasing first and then stabilizing with time, which indicates that the support effect was good and greatly improved the stability and safety of the roadway.